Pro functional PHP programming : application development strategies for performance optimization, concurrency, testability, and code brevity - Aley, Rob (Apress, 2017)
Bring the power of functional programming to your PHP applications. From performance optimizations to concurrency, improved testability to code brevity, functional programming has a host of benefits when compared to traditional imperative programming. Part one of Pro Functional PHP Programming takes you through the basics of functional programming, outlining the key concepts and how they translate into standard PHP functions and code. Part two takes this theory and shows you the strategies for implementing it to solve real problems in your new or existing PHP applications. Functional programming is popular in languages such as Lisp, Scheme and Clojure, but PHP also contains all you need to write functional code. This book will show you how to take advantage of functional programming in your own projects, utilizing the PHP programming language that you already know. You will: Discover functional programming in PHP Work with functional programming functions Design strategies for high-performance applications Manage business logic with functions Use functional programming in object-oriented and procedural applications Employ helper libraries in your application Process big data with functional PHP.